PERBEDAAN HASIL BELAJAR ANTARA METODE OUTDOOR STUDY (JELAJAH ALAM SEKITAR) DENGAN CERAMAH PADA PEMBELAJARAN IPA TEMA BENDA-BENDA DI SEKITAR SEMESTER 1 KELAS V DI SD NEGERI 2 MIMBAAN PANJI SITUBONDO TAHUN PELAJARAN2015/2016 - Uswatun Hasanah; Mory Victor Febrianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
This research is a quantitative research that aims to determine the difference between the methods of outdoor learning outcomes study (natural roaming around) with a lecture on the theme ipa learning objects around half of one domestic class v sd 2 mimbaan banner situbondo the school year 2015/2016. This type of research is a kind of experiment. The population is the total number of members of the study sample that have similar characteristics. Methods of data collection are observation, documentation, and testing. Analysis of the data used in this study include: Knowing the difference in class A (as the class that gets a method of outdoor study (natural roaming around) and class B (as the class that gets lecture method) using the formula ttes. Based on the results and discussion can be summarized as following: the difference between the methods of outdoor learning outcomes study (natural roaming around) with a lecture on the theme of science learning objects around half of 1 class V SD Negeri 2 Mimbaan Panji Situbondo in the school year 2015/2016 amounted to 2,133.